Zooplankton diversity of three dam lakes in Turkey - Saler, S.; Selamoglu, Z. (Iranian Fisheries Science Research Inst-Ifsri, 2020)
[Abstract Not Available]
Keywords: Rotifera; Cladocera; Copepoda; Zooplankton diversity; Dam Lake; Turkey